National strategic development plan : Grenada (The Agency [St. George's]GD)
Addresses a comprehensive range of issues, goals, strategies, objectives and actions that are strategic in charting the course towards the social and economic advancement of Grenada, Carriacou and Petit Martinique.
Keywords: DEVELOPMENT PLANS